Impact properties of cirular beam under lateral loading - Mohammad, Roslina (2006)
Beam elements present simple damage mechanisms when they reach collapse configuration. The deformation characteristics of simply supported circular beams subjected to lateral impact are studied. Such loads tend to lead to large changes in geometry which are accommodated by plastic bending arid shearing within regions of the beams. The study is concerned with the quasi-static bending of various diameter beams by cylindrical-nosed impactors for a variety of support spans. The objective of the present work includes the evaluation of the energy absorbing capacity of beam structures under impact loads. The range of energy-deformation curves and modes of deformation are described. Theoretical models are useful when designing energy-absorbing systems. The influence of material strain-rate sensitivity and system inertia in changing the quasi-static characteristic are discussed. The analytical results are discussed and compared with the experimental results.